2015
DOI: 10.1177/0271121415592411
|View full text |Cite
|
Sign up to set email alerts
|

Coaching Via Electronic Performance Feedback to Support Home Visitors’ Use of Caregiver Coaching Strategies

Abstract: Recommended practices for Part C early childhood special education home visitors encourage use of caregiver coaching strategies to enhance learning opportunities within the natural routines of infants and toddlers. The purpose of this study was to evaluate the effects of a multicomponent professional development intervention on home visitors' use of specific caregiver coaching strategies and range of routines utilized during home-based intervention. The professional development intervention systematically test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 36 publications
0
54
0
Order By: Relevance
“…To support caregivers in embedding instruction, providers must use effective adult learning strategies (Knowles, Holton, & Swanson, 2011). Family-Guided Routines-Based Intervention (FGRBI) has shown promise as an effective and efficient approach for supporting caregivers to embed learning opportunities in everyday routines for children with or at risk of delays in multiple domains (Brown & Woods, 2015, 2016; Krick Osborn & Johnson, 2015). This approach aligns with recommended adult learning and family capacity building strategies by engaging the caregiver as the decision maker; gaining consensus on the child’s learning priorities; using everyday routines and activities as contexts for embedding instruction; providing ongoing caregiver practice with support and feedback; and engaging the caregiver in problem solving, reflection, and planning for how they will embed intervention (Woods, Wilcox, Friedman, & Murch, 2011).…”
mentioning
confidence: 99%
“…To support caregivers in embedding instruction, providers must use effective adult learning strategies (Knowles, Holton, & Swanson, 2011). Family-Guided Routines-Based Intervention (FGRBI) has shown promise as an effective and efficient approach for supporting caregivers to embed learning opportunities in everyday routines for children with or at risk of delays in multiple domains (Brown & Woods, 2015, 2016; Krick Osborn & Johnson, 2015). This approach aligns with recommended adult learning and family capacity building strategies by engaging the caregiver as the decision maker; gaining consensus on the child’s learning priorities; using everyday routines and activities as contexts for embedding instruction; providing ongoing caregiver practice with support and feedback; and engaging the caregiver in problem solving, reflection, and planning for how they will embed intervention (Woods, Wilcox, Friedman, & Murch, 2011).…”
mentioning
confidence: 99%
“…A small group of professionals were successfully trained to teach families how to support their children with strategies embedded in daily routines (Salisbury et al, 2017). Two studies reported adding performance-based feedback or coaching via technology to initial training sessions in efforts to improve the active coaching skills of professionals (Krick Oborn & Johnson, 2015;Marturana & Woods, 2012). These professional development efforts in EI primarily focused on professionals' support and training of families in home visits rather than a package consisting of thorough initial assessment of child and family needs, development of functional, high-quality IFSP outcomes, as well as high-quality home visiting practices.…”
Section: Systems-level Scale-up Of Evidence-based Practicesmentioning
confidence: 99%
“…To test the effect of PD with active engagement and ongoing support, researchers have examined coaching with performance-based feedback to determine the effect on EI providers’ use of targeted practices (Krick Oborn & Johnson, 2015; Marturana & Woods, 2012). Although these researchers have developed unique approaches to effective coaching, a common element has been the delivery of performance-based feedback.…”
Section: Feedback To Enhance Early Intervention (Ei) Provider Practicmentioning
confidence: 99%
“…In addition, these researchers examined the effect of using technology-enhanced, performance-based feedback (TEPF), which incorporates technology and alleviates the challenges associated with face-to-face coaching within Part C, EI environments. This research has been specific to researchers delivering TEPF to EI providers regarding their use of family-centered practices (Krick Oborn & Johnson, 2015; Marturana & Woods, 2012). Krick Oborn and Johnson (2015) examined the effect of using traditional didactic workshops followed by TEPF (email), targeting family engagement practices.…”
Section: Feedback To Enhance Early Intervention (Ei) Provider Practicmentioning
confidence: 99%
See 1 more Smart Citation